La representación fotográfica del cine en Blanco y Negro y ABC (1903-1939) - Tello Díaz, Lucía (Historia y Comunicación Social, 2007)
The introduction of the Cinema in Spain had an irregular development. Since the new invention was shown for the first time in 1896, until it was turned into a popular entertainment, it suffered several adjustments, in order to adapt itself to a Society that, despite its good qualities, was sceptical about the uses of the scientific discovery of the Lumière Brothers in the Entertainment Field. For studying its establishment into the Leisure Culture and the implications of its social diffusion, we are going to analyze the photographic presence of the Cinema into the Spanish Press, especially into the weekly magazine Blanco y Negro and into the daily newspaper ABC. We have chosen this couple because they both symbolize the first attempt into the Periodical to give supremacy to the image. This graphic pre-eminence will show us what the Press paid attention to, and if the Cinema was a remarkable phenomenon for the Media attention, or if it went unnoticed for the journalistic and social universe.